(untitled) (Orinoquia, 2019)
Baby spinach has a high nutritional value, and good entry in specialized markets. Its hydroponic production is limited by nutrient solution, and the aquaponic systems can avoid this limitation. The goal in this work was to evaluate nutrient level changes in hydroponic solution during baby spinach crop. 24 spinach plants were planted in 50 L tanks in floating hydroponic beds, using a modified “La Molina” nutrient solution. They were carried out 5 replications and 3 harvest. Water physicochemical values were registered every week, and plants were harvested after three weeks. Plant samples were also taken before planting (initial time) and after three weeks. Number of leaves, leaf length, leaf area, fresh and dry weight of the aerial part of each plant were recorded. The macronutrient extraction was obtained in descending order: N> P>K+> Ca2+ and micronutrients: Mn2+>Fe2+. pH values were maintained between 6.00-6.97, and DO levels were 4.93-7.54 mg/L. Initial conductivity was about 1558-1592 μS/cm and finally diminished to 1140-1275 μS/cm. CGR= 0.00002-0.00003 g/cm2/day; RGR=0.16, 0.15 y 0.14 g/g/day and NAR=0.006, 0.005 y 0.006 g/cm2/day for replica 1, 2 and 3 respectively. This study reveals that this plant could have good field performance in aquaponic system, especially due to the requirements of N, Ca2+>P, however low amounts of some micronutrients should be added, which are usually scarce in aquaponic systems